Confiding in ChatGPT? Emotional Communication Among Digital Agency Workers with Mobile-AI - Octafiani, Fanny; Wibowo, Octavianus Bima Archa; Irwansyah , Irwansyah (Jurnal Locus Penelitian dan Pengabdian, 2025)
The study explores a new phenomenon in which digital agency workers express their emotions to ChatGPT, marking a shift in human–AI communication patterns. The purpose of this study is to understand how emotional interactions with AI are interpreted and experienced by users in the context of urban work. Using a phenomenological qualitative approach, data was collected through in-depth interviews with four informants who actively use ChatGPT in their professional and personal routines. The results show that ChatGPT is not only seen as a functional work tool, but also as an "emotional safe space", a "digital friend", and a medium for emotion regulation in the face of work pressure. The participants described an affective bond with ChatGPT, which is used as a place for reflection, self-validation, and emotional release. However, this proximity also gives rise to symptoms of emotional dependence as well as the blurring of the boundaries between human empathy and algorithmic responses. The study concludes that ChatGPT serves as a symbolic actor in the digital affection ecosystem—providing emotional support while posing new psychological risks. These findings highlight an important paradox: while AI can improve emotional well-being through expressive mediation, it also reconstructs the meaning of intimacy, empathy, and authenticity in human–technology relationships. The implications of this research extend to the fields of digital ethics, work psychology, and AI design, emphasizing the need to develop emotionally intelligent AI systems to support the well-being of users without creating over-dependence. This research contributes to a deeper understanding of emotional work in the era of artificial mentoring and the social-technological impact